Recent advances in flexible flow sensors and applications - Li Qi’ao; Li Yibo; Xu Kaichen (National Science Open)
Drawing inspiration from natural creatures that utilize flow fluctuations to evade predators and track prey, our human beings harness insights into flow dynamics through the development of flow sensors. The past few decades have witnessed a significant development in such sensors, evolving from bulky catheters designed for industrial settings to miniaturized, versatile and flexible devices tailored for wearable scenarios. This work presents a comprehensive overview of recent advances in flexible and thin-film-based flow sensors. First, the primary working mechanisms of these sensors, including thermal, piezoresistive, piezoelectric, and acoustic principles, are introduced, highlighting their challenges and alternative solutions. Subsequently, applications are categorized and demonstrated based on the type of flow including airflow, blood flow, breath, and water flow. Finally, future trends in flexible flow sensors are explored, indicating their pivotal roles in wide research and industry fields such as underwater robotics, human-machine interfaces, and bioelectronics.